Implementação de princípios e ferramentas lean em laboratório de ensino: uma pesquisa-ação em um laboratório de ensino de construção civil - Santos, Gabriel Alves Rodrigues dos (Universidade Federal de São Carlos, 2025)
Federal public universities have faced significant budgetary constraints since the implementation of a policy in 2016 that limits public spending, making it difficult to modernize laboratories, hire staff, and acquire equipment. In this context, it is essential to adopt management solutions that promote greater efficiency and the rational use of available resources. The Lean philosophy, originally developed in the industrial sector, presents a promising alternative for process optimization in academic environments. Its application in teaching laboratories has gained prominence in international literature, with evidence of significant improvements in organization, waste reduction, and operational efficiency. Tools such as Value Stream Mapping (VSM) and 5S have been successfully applied in university laboratories, particularly in healthcare, although there is a lack of studies focused on civil engineering. This study investigates, through action research, the implementation of Lean principles and tools in a civil engineering teaching laboratory at a federal public university. Workflows were analyzed, key wastes identified, and structural and operational improvements proposed. The interventions resulted in up to 84% reduction in total procedure time, in addition to significant improvements in space organization and activity flow. The data collected and analyzed using both qualitative and quantitative approaches demonstrate the feasibility and benefits of adopting Lean in this type of environment, contributing to both academic literature and university management.
Implementation of lean principles and tools in a teaching laboratory: an action research in a civil engineering teaching laboratory
Keywords: Lean thinking; Laboratório de ensino; Ensino superior; Pesquisa-ação; Mapeamento do fluxo de valor; Teaching laboratories; Higher education; Value stream mapping; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO